Association of glypican‐6 polymorphisms with lumbar disk herniation risk in the Han Chinese population. Issue 7 (20th May 2019) - Hu, Baoyang; Xing, Wenhua; Li, Feng; Huang, Zhi; Zheng, Wenkai; Ji, Demin; Niu, Fanglin; Zhu, Yong; Yang, Xuejun
Abstract: Background: Lumbar disk herniation (LDH) is a degenerative disorder, which partly results from complex genetic factors. The aim of the study was to investigate the potential associations between glypican‐6 ( GPC6 ) variants and LDH risk in Han Chinese population. Methods: A total of 508 Han Chinese LDH patients and 508 healthy controls were recruited in this study. Six single‐nucleotide polymorphisms (SNPs) in GPC6 were selected and genotyped using an Agena MassARRAY platform. We used logistic regression method to evaluate the linkage between GPC6 variants and LDH risk by calculating the odds ratio (OR) and 95% confidence intervals (CIs) in multiple genetic models. HaploReg database was used for SNP functional annotation. Results: Our result revealed GPC6 rs4773724 was associated with a decreased risk of LDH in allele model (OR = 0.82, 95% CI: 0.68–0.98, p  = 0.026), whereas rs1008993 increased the LDH risk (OR = 1.34, 95% CI: 1.05–1.71, p  = 0.020). Besides, we also found rs4773724 and rs9523981 were associated with susceptibility of LDH among individuals whose age are less than 45. And rs1008993 was associated with increased LDH risk in males. Furthermore, Haplotype analysis showed that the TT (rs4773724, rs1008993) haplotype and GC (rs4773724, rs1008993) haplotype had the opposite effects on the susceptibility of LDH. Conclusions: For the first time, we suggest that rs4773724 and rs1008993 in GPC6 were considered as a protective factor and a risk factor for LDH in Han Chinese population, respectively. These results provide new ideas for the treatment and prevention of LDH in Han Chinese population. Abstract : This study reported the potential association of GPC6 polymorphisms with lumbar disk herniation risk in the Han Chinese population for the first time. Our results revealed that rs4773724 and rs1008993 in GPC6 were significant associated with the risk of LDH.